1973
DOI: 10.6028/nbs.ir.73-233
|View full text |Cite
|
Sign up to set email alerts
|

Non-metallic antenna-support materials

Abstract: A bank of six JUUUU-ibf-capacity creep testing machines was designed and is being assembled. These machines, which will accommodate 9-ft specimens, are equipped with environmental chambers for stress-rupture tests up to 200°F under saturated humidity conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1976
1976
1986
1986

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…(3) driving wedges into the ends of the rods prior to potting. The results of these studies [16] showed no improvement over those obtained with the standard Mod 4 end fitting.…”
Section: Development Of the Mod 4 End Fittingmentioning
confidence: 63%
See 2 more Smart Citations
“…(3) driving wedges into the ends of the rods prior to potting. The results of these studies [16] showed no improvement over those obtained with the standard Mod 4 end fitting.…”
Section: Development Of the Mod 4 End Fittingmentioning
confidence: 63%
“…The aluminum-block end fitting was subsequently redesigned [16] in a cylindrical, one-piece configuration, and assigned the laboratory designation H3M. See Figure 9_.…”
Section: Development Of the H3m End Fittingmentioning
confidence: 99%
See 1 more Smart Citation
“…The required tensile loads were applied to the specimens by 30 000lbf (130-kN) capacity, horizontal, dead-weight, lever-arm, creep-testing machines (Figure 8) which can accomodate tensile specimens up to nine feet (2.7 m) long [3]. The test environments were provided by environmental chambers installed in the machines.…”
Section: Test Equipmentmentioning
confidence: 99%